Enhancing criticality and resistance through teaching in the neoliberal academy - Brunila Kristiina; Ikävalko Elina; Honkasilta Juho; Isopahkala-Bouret Ulpukka (PALGRAVE MACMILLAN LTD, 2022)
Academic work and teaching in academia are undergoing major changes in the present neoliberal era. Our purpose in this article is to explore theoretically and in practice how to bring criticality and resistance to life through teaching in the academy and to demonstrate it is not necessarily always a narrative of success. The article is based on our experiences as critical scholars struggling to find ways to contribute to questions of education and social justice, both individually and jointly, over the past 20 years. In this article, we particularly want to examine some of the possibilities and challenges of bringing homo politicus back into the agenda of education.